ARE RESTING EGGS FORMATION IN ROTIFER HEXARTHRA MIRA EFFECT OF CHANGE IN TEMPERATURE? - Suman Kumari; Ram Kumar; U.K. Sarkar; A.P.Sharma; A.K. Jaiswar (Journal of Indian Fisheries Association, 2017)
The dynamics of resting egg formation of the rotifer Hexarthra mira from a wild in the freshwater was investigated. The morphology and the influence of temperature on resting egg formation in Hexarthra mira were carried out during November 2013 to January 2014 in natural environment of small earthen tank area of 10m2 with 1 metre depth in Patna, Bihar, India. The most important environmental factor which influenced resting egg formation in H. mira was water temperature. Resting egg formation, in this rotifer, observed for the first time in the subtropical abandoned earthen tank in natural freshwater environment, is reported in this communication.